Getting a Notch closer to renal dysfunction: activated Notch suppresses expression of the adaptor protein Disabled‐2 in tubular epithelial cells. Issue 1 (27th July 2018) - Schütte-Nütgen, Katharina; Edeling, Maria; Mendl, Gudrun; Krahn, Michael P.; Edemir, Bayram; Weide, Thomas; Kremerskothen, Joachim; Michgehl, Ulf; Pavenstädt, Hermann
ABSTRACT: Reactivation of Notch signaling in kidneys of animal models and patients with chronic kidney disease (CKD) has been shown to contribute to epithelial injury and fibrosis development. Here, we investigated the mechanisms of Notch‐induced injury in renal epithelial cells. We performed genome‐wide transcriptome analysis to identify Notch target genes using an in vitro system of cultured tubular epithelial cells expressing the intracellular domain of Notch1. One of the top downregulated genes was Disabled‐2 ( Dabi ). With the use of Drosophila nephrocytes as a model system, we found that Dab (the Drosophila homolog of Dab 2) knockdown resulted in a significant filtration defect, indicating that loss of Dab2 plays a functional role in kidney disease development. We showed that Dab2 expression in cultured tubular epithelial cells is involved in endocytic regulation and that it also protects cells from TGF‐β‐induced epithelial‐to‐mesenchymal transition. In vivo correlation studies indicated its additional role in renal ischemia‐induced injury. Together, these data suggest that Dab2 plays a versatile role in the kidney and may impact on acute and CKDs.—Schütte‐Nütgen, K., Edeling, M., Mendl, G., Krahn, M. P., Edemir, B., Weide, T., Kremerskothen, J., Michgehl, U., Pavenstädt, H., Getting a Notch closer to renal dysfunction: activated Notch suppresses expression of the adaptor protein Disabled‐2 in tubular epithelial cells. FASEB J. 33, 821–832 (2019). www.fasebj.org